2014
DOI: 10.1111/acel.12269
|View full text |Cite
|
Sign up to set email alerts
|

Growth hormone signaling is necessary for lifespan extension by dietary methionine

Abstract: Summary Growth hormone significantly impacts lifespan in mammals. Mouse longevity is extended when growth hormone (GH) signaling is interrupted but markedly shortened with high plasma hormone levels. Methionine metabolism is enhanced in growth hormone deficiency, e.g. Ames dwarf, but suppressed in GH transgenic mice. Methionine intake affects also lifespan, thus, GH mutant mice and respective wild type littermates were fed 0.16%, 0.43% or 1.3% methionine to evaluate the interaction between hormone status and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
64
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(70 citation statements)
references
References 44 publications
5
64
1
Order By: Relevance
“…Also, methionine restriction increases the stress tolerance of human fibroblasts, reduces senescence and increases their doubling time [66, 67]. In mammals, the effect of MR appears to be growth hormone dependent [68]. …”
Section: Discussionmentioning
confidence: 99%
“…Also, methionine restriction increases the stress tolerance of human fibroblasts, reduces senescence and increases their doubling time [66, 67]. In mammals, the effect of MR appears to be growth hormone dependent [68]. …”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that GH signaling is necessary to discriminate levels of dietary methionine in mice (Brown-Borg et al . 2014). In rodents, protein/amino acid restriction also offers health benefits in models of acute stress and chronic disease.…”
Section: Dietary Interventions Mimicking Calorie Restrictionmentioning
confidence: 99%
“…Restricting a single amino acid such as methionine also increases longevity in normal rats and mice (74,83,119) yet does not impact lifespan in GH signaling mutants (Ames dwarf, GHRKO) (20). Thus intact signaling of the somatotropic pathway appears to be necessary for amino acid sensing in terms of metabolism and lifespan regulation (19).…”
Section: Interventions That Alter Gh or Igf-imentioning
confidence: 99%